EspZ of Enteropathogenic and Enterohemorrhagic Escherichia coli Regulates Type III Secretion System Protein Translocation - Cedric N. Berger (American Society for Microbiology, 2012)
ABSTRACT Translocation of effector proteins via a type III secretion system (T3SS) is a widespread infection strategy among Gram-negative bacterial pathogens. Each pathogen translocates a particular set of effectors that subvert cell signaling in a way that suits its particular infection cycle. However, as effector unbalance might lead to cytotoxicity, the pathogens must employ mechanisms that regulate the intracellular effector concentration. We present evidence that the effector EspZ controls T3SS effector translocation from enteropathogenic (EPEC) and enterohemorrhagic (EHEC) Escherichia coli. Consistently, an EPEC espZ mutant is highly cytotoxic. Following ectopic expression, we found that EspZ inhibited the formation of actin pedestals as it blocked the translocation of Tir, as well as other effectors, including Map and EspF. Moreover, during infection EspZ inhibited effector translocation following superinfection. Importantly, while EspZ of EHEC O157:H7 had a universal “translocation stop” activity, EspZ of EPEC inhibited effector translocation from typical EPEC strains but not from EHEC O157:H7 or its progenitor, atypical EPEC O55:H7. We found that the N and C termini of EspZ, which contains two transmembrane domains, face the cytosolic leaflet of the plasma membrane at the site of bacterial attachment, while the extracellular loop of EspZ is responsible for its strain-specific activity. These results show that EPEC and EHEC acquired a sophisticated mechanism to regulate the effector translocation. IMPORTANCE Enteropathogenic Escherichia coli (EPEC) and enterohemorrhagic E. coli (EHEC) are important diarrheal pathogens responsible for significant morbidity and mortality in developing countries and the developed world, respectively. The virulence strategy of EPEC and EHEC revolves around a conserved type III secretion system (T3SS), which translocates bacterial proteins known as effectors directly into host cells. Previous studies have shown that when cells are infected in two waves with EPEC, the first wave inhibits effector translocation by the second wave in a T3SS-dependent manner, although the factor involved was not known. Importantly, we identified EspZ as the effector responsible for blocking protein translocation following a secondary EPEC infection. Interestingly, we found that while EspZ of EHEC can block protein translocation from both EPEC and EHEC strains, EPEC EspZ cannot block translocation from EHEC. These studies show that EPEC and EHEC employ a novel infection strategy to regulate T3SS translocation.